A Grammatical and Syntactic Analysis of the Structure Section in TOEFL - Deri Fikri Fauzi (English Literature Study Program of Universitas Kebangsaan Republik Indonesia, 2024)
This paper presents an analysis of grammatical competence among English teachers, focusing on their proficiency across various grammatical categories essential for effective instruction. The study reveals significant disparities in understanding, with scores ranging from a low of 34% in negative words to perfect scores of 100% in verb usage, adverb usage, and expletive constructions. While many teachers demonstrate a solid grasp of key structures such as appositives, comparisons, and subject completeness, notable weaknesses in areas like word order and passive voice highlight the need for targeted professional development. The findings suggest that while the average proficiency level is commendable, there are critical gaps that require immediate attention to enhance the overall quality of grammar instruction. To address these weaknesses, the paper recommends the implementation of specialized training programs and collaborative learning opportunities aimed at reinforcing teachers' understanding of challenging grammatical constructs. By fostering a commitment to continuous professional growth, educational institutions can improve teaching practices and ultimately enrich the learning experiences of students, laying a stronger foundation for their language skills.